2024
DOI: 10.1039/d3qi01245j
|View full text |Cite
|
Sign up to set email alerts
|

The chemistry of the s- and p-block elements with 2,2′:6′,2′′-terpyridine ligands

Andreas Winter,
George R. Newkome,
Ulrich S. Schubert

Abstract: The manifold chemistry of terpyridine (tpy) ligands with main-group elements is reviewed not only to provide an overview on this topic but to also inspire intensified research in this often disregarded field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 373 publications
(704 reference statements)
0
2
0
Order By: Relevance
“…Bismuth has become an attractive element toward the design of functional materials due to its nontoxicity as well as its unique electronic and structural properties. For example, Vogler and colleagues proposed that bismuth and other main group metals with closed-shell n s 2 electron configurations could undergo similar photoluminescent transitions to those observed for the d 10 metals. , In fact, more recent work has shown that bismuth–organic compounds have even more versatility as luminescent materials than originally hypothesized; bismuth has been shown to participate in the frontier orbital electronic transitions directly or indirectly by promoting intraligand transitions through its unique coordination chemistry. Notably, bismuth-based metal-to-ligand charge-transfer (MLCT) materials in which the metal directly participates in the electronic transitions have displayed emission across the visible spectrum and exhibited other attractive properties such as mechanochromic luminescence. In 2021, for example, Marshak et al reported a bismuth tris­(benzo­[ h ]­quinoline) (bzq) compound, Bi­(bzq) 3 , that displayed 3 MLCT emission in the blue region .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bismuth has become an attractive element toward the design of functional materials due to its nontoxicity as well as its unique electronic and structural properties. For example, Vogler and colleagues proposed that bismuth and other main group metals with closed-shell n s 2 electron configurations could undergo similar photoluminescent transitions to those observed for the d 10 metals. , In fact, more recent work has shown that bismuth–organic compounds have even more versatility as luminescent materials than originally hypothesized; bismuth has been shown to participate in the frontier orbital electronic transitions directly or indirectly by promoting intraligand transitions through its unique coordination chemistry. Notably, bismuth-based metal-to-ligand charge-transfer (MLCT) materials in which the metal directly participates in the electronic transitions have displayed emission across the visible spectrum and exhibited other attractive properties such as mechanochromic luminescence. In 2021, for example, Marshak et al reported a bismuth tris­(benzo­[ h ]­quinoline) (bzq) compound, Bi­(bzq) 3 , that displayed 3 MLCT emission in the blue region .…”
Section: Introductionmentioning
confidence: 99%
“…Bismuth has become an attractive element toward the design of functional materials due to its nontoxicity as well as its unique electronic and structural properties. 20 27 For example, Vogler and colleagues proposed that bismuth and other main group metals with closed-shell n s 2 electron configurations could undergo similar photoluminescent transitions to those observed for the d 10 metals. 28 , 29 In fact, more recent work has shown that bismuth–organic compounds have even more versatility as luminescent materials than originally hypothesized; bismuth has been shown to participate in the frontier orbital electronic transitions directly or indirectly by promoting intraligand transitions through its unique coordination chemistry.…”
Section: Introductionmentioning
confidence: 99%